A Novel Approach to Enhancing Secure Sharing Using Modified LSB Technique - et. al., R. Rajavarman, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Multiple secret sharing is a method of dividing an image into random shares. With the help of improved LSB technology, the text message is hidden in the cover image and then split into multiple shares. XOR-based multi-secret sharing technique is utilized to securely send pictures from the source to the objective. Multiple secret images can be transmitted at the same time. The access key is shared via email to verify the integrity of the shared information. The secret image can only be displayed after the recipient receives all n shares and decrypts them.